1998
DOI: 10.2134/jeq1998.00472425002700020027x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Sorption Capacities of Wetland Soils and Stream Sediments Impacted by Dairy Effluent

Abstract: The ability of stream sediments and adjacent wetlands to retain added P depends on the P sorption capacity and physico‐chemical properties of sediments or wetland soils. The objectives of this study were to: (i) determine the potential P sorption capacities of wetland soils and stream sediments in systems with distinctly different P loadings, and (ii) establish the relationship between P sorption capacity and selected physico‐chemical properties. Batch sorption isotherms were measured under aerobic and anaerob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(84 citation statements)
references
References 0 publications
8
73
1
1
Order By: Relevance
“…0,10,50,100,200,250,300,350,400 and 500 mg P L -1 . No microbial inhibitors were added to the test systems because they cause the lysis of microbial cells and increase the level of dissolved P in solution (Reddy et al 1998), leading to an underestimation of P sorption (Bridgham et al 2001). There were five replications for each soil treatment (i.e., deep zone, shallow zone, and background).…”
Section: Adsorption Determination Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…0,10,50,100,200,250,300,350,400 and 500 mg P L -1 . No microbial inhibitors were added to the test systems because they cause the lysis of microbial cells and increase the level of dissolved P in solution (Reddy et al 1998), leading to an underestimation of P sorption (Bridgham et al 2001). There were five replications for each soil treatment (i.e., deep zone, shallow zone, and background).…”
Section: Adsorption Determination Methodologymentioning
confidence: 99%
“…Batch incubation experiments were performed to measure the capacity of the wetland soil to remove P from solution, similar to Olsen and Watanabe (1957), Gale et al (1994), and Reddy et al (1998).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Human activities increased external loads, which have accelerated the eutrophication process and triggered internal nutrient loading processes (Reddy et al 1998). As a result, internal loading can delay (Gudimov et al 2012) recovery of water quality even after the external nutrient load has decreased.…”
Section: Comparison With Other Regionsmentioning
confidence: 99%
“…The EPC increases when sediments become anoxic (Reddy et al 1998;Pant and Reddy 2001). House and Denison (2000) found that the EPC of river sediments increased with decreasing redox potential.…”
Section: Introductionmentioning
confidence: 99%